2019
DOI: 10.3390/rs11212490
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Three Different Portable XRF Scanners to Assess the Soil Geochemistry of An Extensive Sample Dataset

Abstract: The assessment of soil elemental concentrations nowadays mainly occurs through conventional laboratory analyses. However, proximal soil sensing (PSS) techniques such as X-ray fluorescence (XRF) spectrometry are proving to reduce analysis time and costs, and thus offer a worthy alternative to laboratory analyses. Moreover, XRF scanners are non-destructive and can be directly employed in the field. Although the use of XRF for soil elemental analysis is becoming widely accepted, most previous studies were limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…For instance, ICP requires the complete digestion of samples using a proper medium which is usually a highly corrosive solution, for example, HF 44,45 . In the case of XRF, it suffers from poor detection limits of light ( Z < 16, Z : atomic number) elements, 46 and quantitative analysis using EDX is known to provide inaccurate data for the samples having multiphase(s) with common elements.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, ICP requires the complete digestion of samples using a proper medium which is usually a highly corrosive solution, for example, HF 44,45 . In the case of XRF, it suffers from poor detection limits of light ( Z < 16, Z : atomic number) elements, 46 and quantitative analysis using EDX is known to provide inaccurate data for the samples having multiphase(s) with common elements.…”
Section: Resultsmentioning
confidence: 99%
“…It may be that the pXRF systematically overestimates S content of the samples and further calibration should have been applied. Systematic overestimation of S (along with P, Cu, and Mg) by pXRF has been observed with field analysis of soils [30]. However, Roman Alday et al [16] found that for samples from the Elatsite porphyry-type deposit, pXRF overestimates Fe and K, and underestimates Mg compared to more intensive laboratory methods.…”
Section: Causes Of Poor Correlationmentioning
confidence: 99%
“…Moreover, thematic geochemical databases have also been established in many countries [14][15][16]. A variety of spatial methods can be applied to produce geochemical patterns using original data stored in a geospatial database [17][18][19]. Shapefile is a geographic information system (GIS) file format developed by the Environmental Systems Research Institute (ESRI), and is the most widely used vector data format to store the location, shape, and attributes of geographical features [20].…”
Section: Introductionmentioning
confidence: 99%